Fading channel equalization using modified complex mininal resource allocation network (CMRAN) - Thiha Kyaw. (2008)
This dissertation introduces an improved version of CMRAN algorithm for fading channel equalization problems. The CMRAN algorithm is combined with an abrupt change detection algorithm and it becomes a new modified CMRAN algorithm. The resultant algorithm is able to track the channel variations and correctly classify the transmitted data from the time-varying channel outputs.